The Effect of Repeat Breeding on the Reproduction Efficiency of Dairy Cattle in Enrekang Regency, South Sulawesi. - Muhuruna, la ode Maksar; Ako, Ambo; Yusuf, Muhammad (Universitas Halu Oleo, 2023)
ABSTRACTThis research aims to know the impact of repeat breeding on the reproduction efficiency of dairy cattle in Enrekang Regency, South Sulawesi. It was conducted from April to November 2021 in Enrekang regency. This research used 102 dairy cattle of Friesian Holstein (FH). The research design used nonprobability sampling with the purposive sampling method. The samples were grouped based on three parities, namely Nuliparous, Primiparous, and Pluriparous. Prevalence data of repeat breeding was obtained from reproduction efficiency evaluation that was seen from a success of the first AI. If pregnancy does not occur in the first AI, it is repeated in the second AI until the third AI. The result shows that the prevalence of repeat breeding in dairy cattle of FH at the parity of Nuliparous had shown a lower percentage (3,44%) compared to the parity of Primiparous and Primiparous (31,57% and 29,62%). The prevalence of the three parities was tangibly different (significant) with p-value <0,05. Reproduction efficiency of dairy cattle of Nuliparous parity was higher than Primiparous and Pluriparous with value S/C (1,5 vs 2,76 vs 2,52) and CR (65,51% vs 47,36% vs 53,70%). The lower the prevalence value of repeat breeding, the better reproduction efficiency.Keywords: Conception Rate, Reproduction Efficiency, Repeat Breeding, Service Per Conception